2016
DOI: 10.1186/s12934-016-0483-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative metabolomics of the thermophilic methylotroph Bacillus methanolicus

Abstract: BackgroundThe gram-positive bacterium Bacillus methanolicus MGA3 is a promising candidate for methanol-based biotechnologies. Accurate determination of intracellular metabolites is crucial for engineering this bacteria into an efficient microbial cell factory. Due to the diversity of chemical and cell properties, an experimental protocol validated on B. methanolicus is needed. Here a systematic evaluation of different techniques for establishing a reliable basis for metabolome investigations is presented.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…It has previously been shown that B. methanolicus uses the SBPase variant of the RuMP cycle [61] and three separate metabolomics studies have identified S7P in methanol grown MGA3 cells [13,34,43]. Our results presented here may indicate that B. methanolicus also possesses an active Ta variant of the RuMP cycle for regeneration of the formaldehyde acceptor Ru5P.…”
Section: Discussionsupporting
confidence: 62%
“…It has previously been shown that B. methanolicus uses the SBPase variant of the RuMP cycle [61] and three separate metabolomics studies have identified S7P in methanol grown MGA3 cells [13,34,43]. Our results presented here may indicate that B. methanolicus also possesses an active Ta variant of the RuMP cycle for regeneration of the formaldehyde acceptor Ru5P.…”
Section: Discussionsupporting
confidence: 62%
“…Since methanol is more reduced than glucose, it supports production of reduced compounds. Although omics data of native methylotrophs have been generated in the past decade [6,15,16,27], natural methanol utilization has not yet been fully understood, which makes the transfer of methylotrophy to non-methylotrophs a demanding challenge [5,19]. Here, we developed methanol-dependent C. glutamicum strains through rpe and rpi deletions that functioned as metabolic cut-offs to force methanol-utilization for biomass formation ( Figure 1A,B).…”
Section: Methanol-dependent Complementation Of a Ribose 5-phosphate Imentioning
confidence: 99%
“…Although there have been recent advances in the development of tools for system engineering of B. methanolicus [15][16][17], the genetic toolbox for these methylotrophic bacteria is still limited and metabolic engineering to optimize carbon fluxes for increased product titers or yields remains a challenge to this day [18]. Thus, the demand to transfer methylotrophy to mesophilic bacteria with well-established engineering toolset has been high in recent years [19].…”
Section: Introductionmentioning
confidence: 99%
“…; Carnicer et al . ; Patejko et al . ), can therefore be used to detect and qualitatively and quantitatively characterize discriminatory metabolite features with nematicidal potential.…”
Section: Using Metabolomics To Detect Possible Nematicidal Compoundsmentioning
confidence: 99%
“…In this context, the identification of a feature means that the feature was identified as a discriminatory feature explaining the statistical differences between metabolite profiles from different Bacillus species. Metabolomics, defined as the comprehensive analysis of all the metabolites present within an organism (Villas-Bôas et al 2007;Carnicer et al 2016;Patejko et al 2017), can therefore be used to detect and qualitatively and quantitatively characterize discriminatory metabolite features with nematicidal potential.…”
Section: Using Metabolomics To Detect Possible Nematicidal Compoundsmentioning
confidence: 99%